Reduced Baseline Airway Caliber Relates to Larger Airway Sensitivity to Rostral Fluid Shift in Asthma - Bhatawadekar, Swati A.; Keller, Gabriel; Francisco, Cristina O.; Inman, Mark D.; Fredberg, Jeffrey J.; Tarlo, Susan M.; Stanbrook, Mathew; Lyons, Owen D.; Yadollahi, Azadeh (Frontiers in Physiology, 2017)
Background: We have previously shown that when the asthmatics go supine, fluid shifts out of the legs, accumulates in the thorax, and exacerbates lower airway narrowing. In the retrospective analysis of our previous work presented here, we test the hypothesis that the sensitivity of this process relates inversely to baseline caliber of the lower airways. Methods: Eighteen healthy (6 women) and 16 asthmatic subjects (9 women) sat for 30 min, and then lay supine for 30 min. While supine, lower body positive pressure (LBPP, 40 mm Hg) was applied to displace fluid from the legs similar in amount to the overnight fluid shift. Respiratory resistance and reactance at 5 Hz (R5 and X5) and leg and thoracic fluid volumes (LFV and TFV) were measured at the beginning and end of the supine period. Results: With LBPP, healthy and asthmatic subjects had similar changes in the LFV and TFV (p=0.3 and 0.1 respectively). Sensitivity to fluid shift, defined by ∆R5/∆TFV, was larger in the asthmatics than in the healthy subjects (p=0.0001), and correlated with baseline R5 in the supine position in the asthmatics (ρ=0.7, p=0.003). No such association was observed in the healthy subjects (p=0.6). In the asthmatics, women showed a greater reduction in X5 than men with LBPP (p=0.009). Conclusions: Smaller baseline airway caliber, as assessed by larger R5, was associated with increased sensitivity to fluid shift in the supine position. We conclude that asthmatics with narrower small airways such as obese asthma patients, women with asthma, and those with severe asthma may be more sensitive to the effects fluid shift while supine as during sleep.